2016
DOI: 10.1111/nmo.12785
|View full text |Cite
|
Sign up to set email alerts
|

Novel nervous system mechanisms in visceral pain

Abstract: Visceral hypersensitivity is an important factor underlying abdominal pain in functional gastrointestinal disorders such as irritable bowel syndrome (IBS) and can result from aberrant signaling from the gut to the brain or vice versa. Over the last two decades, research has identified several selective, intertwining pathways that underlie IBS-related visceral nociception, including specific receptors on afferent and efferent nerve fibers such as transient receptor potential channels (TRP) channels, opioid, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
(109 reference statements)
0
19
0
Order By: Relevance
“…These opioids signal to G i/o -coupled μ-opioid, δ-opioid and κ-opioid receptors on nociceptive neurons, decreasing excitability and the release of neuropeptides. These receptors are found at multiple sites in the nociceptive neural pathway to the central nervous system (CNS),9 11 including an action on descending inhibitory neurons in the spinal cord. However, the actions of endogenous opioids generated in peripheral tissues predominantly target the peripheral terminals of DRG neurons 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These opioids signal to G i/o -coupled μ-opioid, δ-opioid and κ-opioid receptors on nociceptive neurons, decreasing excitability and the release of neuropeptides. These receptors are found at multiple sites in the nociceptive neural pathway to the central nervous system (CNS),9 11 including an action on descending inhibitory neurons in the spinal cord. However, the actions of endogenous opioids generated in peripheral tissues predominantly target the peripheral terminals of DRG neurons 4.…”
Section: Introductionmentioning
confidence: 99%
“…Stress hormones and the sympathetic nervous system have immunomodulatory roles16 17 and, depending on the level of activation, can exert either inhibitory or excitatory effects. Several studies suggest that sympathetic postganglionic outflow facilitates peripheral pain signalling by acting on α-adrenoceptors11 18 19 and in the spinal cord can interact with endogenous opioids. In animal models and carefully designed human IBD studies,4 20 21 stress is also associated with a greater risk of disease relapse.…”
Section: Introductionmentioning
confidence: 99%
“…66,67 MCs and histamine seem to contribute majorly to visceral hypersensitivity. A study on H 1 R knockout mice showed that they are more prone to visceral pain, measured by abdominal stretching after intraperitoneal injection of either acetic acid or MgSO 4 than their wild type littermates.…”
Section: Possible Application Of Anti-histamine Drugs In Irritable Bomentioning
confidence: 99%
“…The vagus nerve is largely an afferent nerve, and it influences GI motility, hunger/satiety, and visceral nociception. There is an increasing appreciation that the sympathetic and parasympathetic nervous systems broadly exert pro‐ and antinociceptive actions within the human viscera . The neurobiological mechanisms of vagal‐mediated analgesia within the viscera remain incompletely understood.…”
Section: Parasympathetic Modulation Of Esophageal Painmentioning
confidence: 99%
“…There is an increasing appreciation that the sympathetic and parasympathetic nervous systems broadly exert pro-and antinociceptive actions within the human viscera. 2 The neurobiological mechanisms of vagal-mediated analgesia within the viscera remain incompletely understood. However, a number of putative mechanisms have been proposed, including, but not limited to, the cholinergic anti-inflammatory pathway in the periphery 3 and alterations within the hypothalamic-pituitaryadrenal axis and centrally within the brain stem at the nucleus of the solitary tract and the central autonomic network.…”
Section: Parasympathetic Modulation Of Esophageal Painmentioning
confidence: 99%